Fiscal Multipliers in Recessions. (29th January 2016) - Canzoneri, Matthew; Collard, Fabrice; Dellas, Harris; Diba, Behzad
Abstract : Standard business cycle models have difficulties generating large, state‐dependent fiscal multipliers. Employing a model of costly financial intermediation based on Curdia–Woodford, we show that fiscal multipliers can be strongly state dependent: fiscal expansions during recessions may lead to multiplier values exceeding two, while similar expansions during economic booms would produce values falling short of unity. This pattern obtains if the spread (the financial friction) is more sensitive to fiscal policy during recessions than during expansions, a feature that is present in the data. Our results are consistent with recent empirical work documenting the state contingency of multipliers.